Factors influencing employee silence in higher learning institutions in Malaysia: a preliminary study - Musa, Norimah; Wok, Saodah (2019)
Employee silence exists in many organizations resulting from the organizational culture itself, workplace bullying, or power differential that exists between superiors and subordinates. As such, this study tries to examine the existence of employee silence which may have a negative effect on the organization’s image, reputation, productivity, and profitability. The objectives of the study are (1) to find out the extent of the existence of organizational culture, workplace bullying, and power differential among employees of a higher learning institutions; (2) to determine the level of employee silence experienced; (3) to analyze the relationship between organizational culture, workplace bullying, power differential, and employee silence; and (4) to determine the best predictor for the existence of employee silence. The pilot study was conducted at Open University Malaysia (OUM) involving 50 respondents using the survey method with the questionnaire as the research instrument for data collection. Results show that the employees experience positive organizational culture while power differential and workplace bullying are comparatively less prevalent. However, employee silence does exist to certain extent. There is a positive relationship between workplace bullying and power differential but not with employee silence. Hence, the spiral of silence theory does not apply to the academic sphere.